A randomised controlled pilot study: the effectiveness of narrative exposure therapy with adult survivors of the Sichuan earthquake - Zang, Yinyin; Hunt, Nigel; Cox, Tom (BioMed Central, 2013)
Background: Post-Traumatic Stress Disorder (PTSD) is a common psychological reaction after large-scale natural disasters. Given the number of people involved and shortage of resources in any major disaster, brief, pragmatic and easily trainable interventions are needed. The aim of this study is to evaluate the efficacy of Narrative Exposure Therapy (NET) as a short-term treatment for PTSD using Chinese earthquake survivors. Methods: A randomized waiting-list control pilot study was conducted between December 2009 and March 2010, at the site of the Sichuan earthquake in Beichuan County, China. Adult participants with newly diagnosed Post Traumatic Stress Disorder (PTSD) were randomly allocated to Narrative Exposure Therapy (NET) or a Waiting-List (WL) condition. The latter received NET treatment after a two-week waiting period. To compare the effectiveness of NET in traumatised earthquake survivors, both groups were assessed on PTSD symptoms, general mental health, anxiety and depression, social support, coping style and posttraumatic change before and after treatment and two months post treatment. Results: Adult participants (n=22) were randomly allocated to receive NET (n=11) or WL (n=11). Twenty two participants (11 in NET group, 11 in WL) were included in the analysis of primary outcomes. Compared with WL, NET showed significant reductions in PTSD symptoms, anxiety and depression, general mental stress and increased posttraumatic growth. The WL group later showed similar improvements after treatment. These changes remained stable for a two-month follow-up. Measures of social support and coping showed no stable effects. Conclusions: NET is effective in treating post-earthquake traumatic symptoms in adult Chinese earthquake survivors. The findings help advance current knowledge in the management of PTSD after natural disasters and inform future research. Larger sample sizes are needed to extend the present findings. Trial registration: Chinese Clinical Trial Registry ChiCTR-TRC-12002473 Keywords: Earthquake, Exposure, Disaster, Narrative, PTSD, Therapy